2017
DOI: 10.22608/apo.201616
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Steroid-Induced Cataract and Glaucoma in Chronic Obstructive Pulmonary Disease Patients Attending a Tertiary Care Center in India

Abstract: It is evident that higher doses and longer duration of inhaled corticosteroid in COPD patients are associated with a higher prevalence of cataract and glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 8 publications
1
20
1
5
Order By: Relevance
“…Indeed, a constant oxygen supply is crucial for adequate organ function 44 ., andeven small changes in oxygen supply to the retina can result in tissue hypoxia and retinal changes 44 . In addition, exposure to corticosteroids may contribute to an increased risk of glaucoma and cataract, though results in patients with COPD are contradictory [45][46][47] . An earlier review demonstrated that structural and functional changes in the retinal microvasculature are more common and severe in patients with COPD compared to non-COPD controls, including increased retinal vessel diameter, lower retinal arterial oxygen saturation, impaired haemodynamics and increased resistive index of the orbital vessels 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a constant oxygen supply is crucial for adequate organ function 44 ., andeven small changes in oxygen supply to the retina can result in tissue hypoxia and retinal changes 44 . In addition, exposure to corticosteroids may contribute to an increased risk of glaucoma and cataract, though results in patients with COPD are contradictory [45][46][47] . An earlier review demonstrated that structural and functional changes in the retinal microvasculature are more common and severe in patients with COPD compared to non-COPD controls, including increased retinal vessel diameter, lower retinal arterial oxygen saturation, impaired haemodynamics and increased resistive index of the orbital vessels 43 .…”
Section: Discussionmentioning
confidence: 99%
“…The difference in IOP was statistically significant ( p < 0.001), although it was small: the observed pressure was 15.31 ± 3.27 mmHg for the inhaled glucocorticoid group versus 13.39 ± 1.95 mmHg for the control group. The study conducted by Nath et al in 2017 showed 57 out of 405 subjects to have had an IOP higher than 22 mmHg after the intake of inhaled glucocorticoids, although no mention of statistical significance was made [ 33 ]. The eight remaining articles did not show any significant effect of inhaled glucocorticoids on IOP [ 11 , 18 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…The reason of the discrepancy might be lower dosage of daily ICS and relatively smaller number of subjects in our study compared to the previous studies. 37 , 38 …”
Section: Discussionmentioning
confidence: 99%